PENGARUH PENGGUNAAN APLIKASI KAHOOT TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN PANCASILA DI SMA SWASTA PADANG BULAN KELAS IX T.P 2026-2027 - Hasibuan, Mantasia; Sri Yunita; Sampitmo Habeahan; Surya Dharma; Liber Siagian (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study looks into how using the Kahoot app affects students' performance in Pancasila Education at GKPI Padang Bulan Private High School. The reason for this study is that students are not achieving good results in their learning, which is because the usual teaching methods are not interesting and there is not much use of technology in the materials used for learning. This study uses a quantitative method with a quasi-experimental setup, where a pretest and posttest are conducted, and the control group is not the same size as the experimental group. The sample used consisted of two classes. The experimental group used the Kahoot app, and the control group used regular teaching methods. Data was gathered using learning achievement tests, which had both a pretest and a posttest. The results were checked with normality tests, homogeneity tests, independent sample t-tests, and N-Gain tests. Before the treatment started, there was no big difference in the abilities of students in the experimental class and the control class. Once the learning was done, the experimental class used the Kahoot app as a game-based learning tool, while the control class kept using traditional teaching methods. Using Kahoot can help make learning more fun, interesting, and competitive. This helps students get involved more, makes them more excited about learning, and makes it easier for them to understand the Pancasila Education material. The research shows that using the Kahoot app makes a big difference in how well students learn. The average score before the experiment in the class was 34.43, and it went up to 80.87 after the experiment. Meanwhile, the average score before the test in the control class was 36.70, but it went up to 68.70 after the test. The results from the Independent Sample t-Test showed a significance value (two-tailed) of 0.000, which is lower than 0.05 This means we accept the alternative hypothesis and reject the null hypothesis. The N-Gain analysis results showed that the experimental class had an average increase in learning outcomes of 0.7114, which is considered high, while the control class had an average increase of 0.5073, which is considered moderate. In summary, using the Kahoot app has a big and better effect on helping students perform well in Pancasila Education. Pancasila at GKPI Padang Bulan Private High School. Sebelum perlakuan diberikan, kemampuan awal siswa di kelas eksperimen dan kelas kontrol hampir tidak berbeda secara signifikan. Setelah pembelajaran selesai, kelas eksperimen menggunakan aplikasi Kahoot sebagai sarana belajar yang berupa permainan, sedangkan kelas kontrol masih menerapkan metode belajar biasa. Menggunakan Kahoot dapat menciptakan suasana belajar yang lebih menarik, menyenangkan, dan berbasis kompetisi. Hal ini membuat siswa lebih tertarik untuk ikut berpartisipasi aktif, meningkatkan semangat belajar mereka, serta memudahkan pemahaman terhadap materi Pendidikan Pancasila. Temuan penelitian menunjukkan bahwa pemanfaatan aplikasi Kahoot memberikan dampak yang signifikan terhadap hasil belajar siswa. Rata-rata nilai pretest di kelas eksperimen adalah 34,43, yang kemudian meningkat menjadi 80,87 pada posttest. Sementara itu, rata-rata nilai pretest di kelas kontrol sebesar 36,70 berkembang menjadi 68,70 pada posttest. Hasil uji Independent Sample t-Test menunjukkan nilai Sig.(2-tailed) sebesar 0,000, yang lebih kecil dari 0,05, sehingga. hipotesis alternatif diterima dan hipotesis nol ditolak. Selain itu, hasil analisis N-Gain menunjukkan rata-rata peningkatan hasil belajar di kelas eksperimen mencapai 0,7114, yang masuk dalam kategori tinggi, sedangkan kelas kontrol mencapai 0,5073 dalam kategori sedang. Dengan demikian, dapat disimpulkan bahwa penerapan aplikasi Kahoot memiliki pengaruh yang cukup besar dan lebih efektif dalam meningkatkan hasil belajar siswa pada mata pelajaran Pendidikan Pancasila di sekolah menengah swasta.​dinyatakan bahwa adopsi​​​Aplikasi Kahoot memiliki pengaruh yang cukup besar dan lebih efektif dalam meningkatkan hasil belajar siswa pada mata pelajaran Pendidikan Pancasila di sekolah menengah. di SMA Swasta GKPI Padang Bulan.